Borders. Children’s literature and its intersections - Beseghi, Emma (img journal, 2019)
Children’s literature travels from one era to another, from one age to another (from early childhood to early adulthood), overcoming boundaries thanks to the many translations, while it is crossed by several genres and is contamined by them. For a long time, children’s literature has been combined with the creation of metaphors. Childhood metaphors that represent the best way to penetrate and investigate the shadowlands of the childhood universe beyond the thick and homologating mist that makes it invisible. In particular, the picture books, of which the wordless or silent books represent the most innovative aspect, are considered the main instruments in children’s literature for the stunning aesthetic quality that connotes them.